AN EAST ASIAN MATHEMATICAL CONCEPTUALIZATION OF THE TRANSHUMAN. - Woosik, Hyun (Zygon: Journal of Religion & Science, 2016)
This study explores the transhuman from an East Asian perspective. In terms of cognitive science, mathematics, and theology, we define the transhuman system as characterized by (1) transcendence, (2) extension by compactification, and (3) samtaegeuk. Compactification is conceptualized here in mathematical terms, as adding one or more elements so that a system becomes more complete-as one might join both ends of a line, and thereby create a circle. We assert that the East Asian transhuman could be defined as a three-point compactification: (1) as an extension of biophysical objects and events such as robots, cyborgs, and environments (Earth); (2) as an extension of culture, science, and art (Human); and (3) as an extension of the interaction between the human and Cosmic Absolute such as in religions. Such a notion of the Transhuman might be associated with God, but any description of God, the Absolute Infinite, will apply to something less than God.